Gli Open Geodata e la regione Toscana (GEOmedia, 2015)
La Regione Toscana e le altre Regioni operano in ottemperanza ad un contesto normativo che individua il rilascio dei dati geografici come Open GeoData quale condizione necessaria per favorire Trasparenza, Partecipazione e Collaborazione. L'attivazione di Open Services come previsto dalla Direttiva Inspire è di fondamentale importanza per favorire la fruizione dell'enorme patrimonio conoscitivo.The Tuscan Region and other regions operate in compliance with a regulatory framework that identifies the release of geographical data as Open GeoData as a necessary condition to promote transparency, participation and collaboration. The availability of spatial and environmental data occurs not only through the release of compressed packets to download, but also through the activation of Open Services as required by Inspire Directive, and evolves more and more towards Open Knowledge in an attempt to encourage the enjoyment of the enormous wealth of information collected.